Diagnóstico y planes de mejoramiento de los procedimientos contables del manejo de efectivo y cuentas por cobrar de la cadena de Droguerías Comfenalco Quindío en las ciudades de Calarcá y Armenia (2012)
Comfenalco Quindio is a Family Compensation Fund with 45 years as the leader organization in the region. Its main corporate purpose is the redistribution of 4% of the non-fiscal contributions paid by employers for the lower-income workers in the region. One of its business units is the Marketing Division, consisting of 8 drugstores strategically located in the cities of Armenia and Calarca Quindio, which provide high quality medicines at reasonable prices.